Behavioral Inputs to the Theoretical Approach of the Economic Crisis - Sinziana Baltatescu (CES Working Papers, 2015)
The current economic and financial crisis gave room for the theoretical debates to reemerge. The economic reality challenged the mainstream neoclassical approach leaving the opportunity for the Austrian School, Post Keynesianism or Institutionalists to bring in front theories that seem to better explain the economic crisis and thus, leaving space for more efficient economic policies to result. In this context, the main assumptions of the mainstream theoretical approach are challenged and reevaluated; behavioral economics is one of the main challengers. Without developing in an integrated school of thought yet, behavioral economics brings new elements within the framework of economic thinking. How are the main theoretical approaches integrating these new elements and whether this process is going to narrow the theory or enrich it to be more comprehensive are questions to which this paper tries to answer, or, at least, to leave room for an answer.
Keywords: D03; G01; 330; neoclassical approach; economics crisis; behavioral economics